THE URGENCY AND REVITALIZATION OF THE DEVELOPMENT OF THE ECONOMIC SYSTEM IN INDONESIA THROUGH THE MANAGEMENT OF THE SCIENTIFIC APPROACH OF FIQH PESANTREN - Moch. Rusli; Ikhda Khullatil Mardliyah (Universitas Muhammadiyah Surakarta, 2023)
Economics has become an essential science for the resilience of a country and has become an endless discussion. The Prophet exemplified economic activity before the prophetic era, and economic studies emerged in fiqh learning which was divided into muamalah fiqh. Muamalah fiqh studies can be found in Islamic boarding schools, but the snag is part of the final chapter in one book study, so the depth of the material still needs to be improved. The main objective of this research is to explain the urgency and revitalization of Islamic boarding school fiqh as the basis for economic activity in Indonesia so that the Indonesian economy can survive and be sustainable. This research is qualitative descriptive research with a data source in the form of a document review. Data analysis techniques use Creswell's theory: of organizing, transcribing, and analyzing data. The results show that pesantren, with all the potential they have, can revitalize Islamic boarding schools with economics using the scientific approach to jurisprudence that has been studied. This revitalization is essential to be carried out comprehensively following current economic developments while still using the sources of the Qur'an and Hadith.